Kinematic and electromyographic changes during 200 m front crawl at race pace - Figueiredo, P.; Sanders, R.; Gorski, T.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Medicine, 2013)
The purpose of this study was to analyse eventual kinematic and electromyographic changes during a maximal 200 m front crawl at race pace. 10 male international level swimmers performed a 200 m maximal front crawl test. Images were recorded by 2 above and 4 under water cameras, and electromyographic signals (EMG) of 7 upper and lower limbs muscles were analysed for 1 stroke cycle in each 50 m lap. Capillary blood lactate concentrations were collected before and after the test. The variables of interest were: swimming speed, stroke length, stroke and kick frequency, hand angular velocity, upper limb and foot displacement, elbow angle, shoulder and roll angle, duration of stroke phases, and EMG for each muscle in each stroke phase. Generally, the kinematic parameters decreased, and a relative duration increased for the entry and pull phases and decreased for the recovery phase. Muscle activation of flexor carpi radialis, biceps brachii, triceps brachii, peitoral major and upper trapezius increased during specific stroke phases over the test. Blood lactate concentration increased significantly after the test. These findings suggest the occurrence of fatigue, characterised by changes in kinematic parameters and selective changes in upper limbs muscle activation according to muscle action.